CRAN-29. CONSERVATIVE SURGERY FOLLOWED BY PROTON THERAPY FOR CRANIOPHARYNGIOMA IN CHILDREN: A PHASE II STUDY TO EXAMINE THE FEASIBILITY OF DOSE ESCALATION. Issue 2 (22nd June 2018) - Alapetite, Claire; Puget, Stephanie; Nauraye, Catherine; Beccaria, Kevin; Bolle, Stephanie; Lesueur, Paul; Brisse, Hervé; Boddaert, Nathalie; Dendale, Remi; Doz, François; Rose, Christian Sainte; Bouffet, Eric; et al.
Abstract: Optimal treatment for pediatric craniopharyngioma remains controversial. Although conservative surgery followed by radiation is favored, particularly when hypothalamic infiltration. Proton beam therapy (PT) offers further sparing of normal tissues exposure compared to photons. The objectives of this study were; To assess the efficacy of limited surgery followed by PT in children with craniopharyngioma; To evaluate feasibility of dose escalation while maintaining risk-adapted dose constraints to the chiasm. The trial included 33 patients (17 males), median age 9.0 years (2.1–15.5) at diagnosis, 9.6 years (3.3–15.8) at radiation. All patients underwent surgery (1–5, median: 2) with measurable residue. Median interval between diagnosis and PT was 7.2 months (2.5–73.6). Median PTV was 31.1 cm3 (12.7–136). Imaging studies during radiation identified increase in size of cystic components in 11 patients, including 2 who required re-planning. Total median dose was 54.4 CGE (52.2–56.1). Based on dosimetric parameters, 5 patients underwent slight dose escalation. Median dose to the chiasm was 52.7 CGE (51.8–54.4). At a median follow-up of 4.3 years (1.3–7.0) since radiation, 32 patients are alive. 3 patients experienced progression. All patients are on hormone replacement, 25/32 patients have normal vision in at least one eye, 17/32 have restricted fields. 24 patients have normal academic status, 8 patients require special schooling. Median BMI is 24.1 (18.7–36.3), 11 patients are overweight and 9 obese. CONCLUSION: This study supports the use of PT in pediatric craniopharyngioma, although the objective of dose escalation, using passive scattering delivery was not reached, preventing dose effect relationship evaluation.